PENINGKATAN KEMAMPUAN MENULIS CERITA MELALUI MEDIA GAMBAR BERSERI PADA MURID KELAS IV-B UPT SDN 145 GRESIK - Pertiwi, Septi Eka; Prastyo, Danang; Chomsiyah, Siti; Ananda, Refilia Tri; Rahmawati, Selfe; Shoberina Iliyin; Rohmah, Shofi Al Himmah Yudatu; Oktavia, Winda Krisna (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The storytelling writing skills of Grade IV-B students at UPT SDN 145 Gresik were still not optimal, particularly in developing ideas, organizing story plots, and using correct spelling and punctuation. This study aimed to improve students’ storytelling writing skills through the use of serial picture media among 29 students of Grade IV-B at UPT SDN 145 Gresik. This research employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, which was conducted in two cycles consisting of the stages of planning, implementation, observation, and reflection. Data collection techniques included observation, tests, and documentation, while the data were analyzed using descriptive quantitative and qualitative methods. The results showed an improvement in classical learning mastery from 41% in the pre-cycle to 62% in Cycle I, and further increased to 90% in Cycle II. Students’ activities and participation also improved during the learning process. Therefore, serial picture media proved to be effective in improving students’ storytelling writing skills through more active and meaningful learning.